2014
DOI: 10.1093/cid/ciu340
|View full text |Cite
|
Sign up to set email alerts
|

School-Located Influenza Vaccination Decreases Laboratory-Confirmed Influenza and Improves School Attendance

Abstract: Vaccination of at least a quarter of the school population resulted in decreased influenza rates and improved school attendance. Herd immunity for unvaccinated children may occur in schools with vaccination coverage approaching 50%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 32 publications
(37 reference statements)
5
59
2
6
Order By: Relevance
“…9 Other studies have reported significant VE for LAIV against outpatient and inpatient medically attended H1N1pdm09-related illness among school-aged children in the United States in 2009 to 2010 and 2010 to 2011. 2426 However, reduced LAIV effectiveness against A/H1N1pdm09 was observed during 2010 to 2011 among adults in the US military. 27 One Canadian study reported effectiveness of trivalent LAIV against influenza A during the 2013–2014 season; however, the study had few participants who received LAIV.…”
Section: Discussionmentioning
confidence: 99%
“…9 Other studies have reported significant VE for LAIV against outpatient and inpatient medically attended H1N1pdm09-related illness among school-aged children in the United States in 2009 to 2010 and 2010 to 2011. 2426 However, reduced LAIV effectiveness against A/H1N1pdm09 was observed during 2010 to 2011 among adults in the US military. 27 One Canadian study reported effectiveness of trivalent LAIV against influenza A during the 2013–2014 season; however, the study had few participants who received LAIV.…”
Section: Discussionmentioning
confidence: 99%
“…One fifth of the children received influenza vaccine though the SLV programs or at a community site as documented in CAIR (Table 2). Most (83.1%) received LAIV, which the SLV program gave preferentially (17). We compared outcomes of obese children with different groupings of non-obese categories including: healthy weight alone, healthy weight and underweight, and overweight, healthy weight, and underweight.…”
Section: Resultsmentioning
confidence: 99%
“…Data were analyzed from a previously conducted prospective study to evaluate the impact of school-located influenza vaccination (SLV) programs on influenza rates and absenteeism (17). The original study group consisted of 4,455 children enrolled in eight elementary schools in two Los Angeles County (LAC) school districts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations